Reduced Representation and Whole‐Genome Sequencing Approaches Highlight Beluga Whale Populations Associated to Eastern Canada Summer Aggregations - Luca Montana; Trevor T. Bringloe; Audrey Bourret; Caroline Sauvé; Arnaud Mosnier; Steven H. Ferguson; Lianne Postma; Véronique Lesage; Cortney A. Watt; Mike O. Hammill; Geneviève J. Parent (Evolutionary Applications)
ABSTRACT Effective conservation strategies inherently depend on preserving populations, which in turn requires accurate tools for their detection. Beluga whales (Delphinapterus leucas) inhabit the circumpolar Arctic and form discrete summer aggregations. Previous genetic studies using mitochondrial and microsatellite loci have delineated distinct populations associated to summer aggregations but the extent of dispersal and interbreeding among these populations remains largely unknown. Such information is essential for the conservation of populations in Canada as some are endangered and harvested for subsistence by Inuit communities. Here, we used reduced representation and whole‐genome sequencing approaches to characterize population structure of beluga whales in eastern Canada and examine admixture between populations. A total of 905 beluga whales sampled between 1989 and 2021 were genotyped. Six main genomic clusters, with potential subclusters, were identified using multiple proxies for population structure. Most of the six main genomic clusters were consistent with previously identified populations, except in southeast Hudson Bay where two clusters were identified. Beluga summer aggregations may consequently be comprised of more than one distinct population. A low number of dispersers were identified between summer aggregations and limited interbreeding was detected between the six genomic clusters. Our work highlights the value of genomic approaches to improve our understanding of population structure and reproductive behavior in beluga whales, offering insights applicable to other cetacean species of conservation concern. An expansion of the geographical scope and increase in number of genotyped individuals will, however, be needed to improve the characterization of the finer scale structure and of the extent of admixture between populations.